Effects of Suction and Blowing on Flow Separation in a Symmetric Sudden Expanded Channel - Layek, G. C. C.; Midya, C.; Mukhopadhyay, S. (Nonlinear Analysis: Modelling and Control, 2008)
A numerical simulation has been carried out to study the laminar flow in a symmetric sudden expanded channel subjected to a uniform blowing/suction speed placed at the lower and upper porous step walls. The governing equations for viscous flow have been solved using finite-difference techniques in pressure-velocity formulation. The results obtained here have been compared with the available experimental and numerical results of similar problems. It is noted that the recirculating region formed near the step walls diminishes in its length for increasing values of blowing speed applied at the porous step walls. For a suitable blowing speed, the recirculation zone disappears completely. The critical Reynolds number for the flow bifurcation (i.e. flow asymmetry) is obtained and it increases with the increase of the blowing speed. The critical Reynolds number for symmetry breaking of the flow decreases with the increasing values of suction speeds. The primary and the secondary recirculating regions formed near the channel walls are controlled using blowing.
Keywords: sudden expansion; porous step walls; staggered grid